2021
DOI: 10.4178/epih.e2021048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tobacco outlet density on quit attempts in Korea: a multi-level analysis of the 2015 Korean Community Health Survey

Abstract: OBJECTIVES This study aimed to examine whether the regional density of tobacco outlets in Korea was associated with the likelihood of attempting to quit among smokers METHODS This study was designed as a secondary data analysis of a cross-sectional study. Data from the 2015 Korean Community Health Survey and tobacco outlet registrations in 17 metropolitan cities and provinces with 254 communities in Korea were used for the analysis. In total, 41,013 current smokers (≥19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…While explaining 4•86% of the concerns in area-level, which is somewhat noticeable where the majority of previous research populated in South Korea indicated little explanation of regional variation to health-related outcomes (around 3%). [27][28][29][30] Other characteristics of individuals that had signi cant associations with the concern, which are in line with existing research, are; women, [31] older, [31][32][33] lower income, [34] lower education, [31] perceived health status, [32] and current depressive symptom. [32,35] The association between ADI and the concern related to COVID-19 differed by age groups of 19-29, 30-39, and 40-49, which are the economically active population.…”
Section: Discussionsupporting
confidence: 64%
“…While explaining 4•86% of the concerns in area-level, which is somewhat noticeable where the majority of previous research populated in South Korea indicated little explanation of regional variation to health-related outcomes (around 3%). [27][28][29][30] Other characteristics of individuals that had signi cant associations with the concern, which are in line with existing research, are; women, [31] older, [31][32][33] lower income, [34] lower education, [31] perceived health status, [32] and current depressive symptom. [32,35] The association between ADI and the concern related to COVID-19 differed by age groups of 19-29, 30-39, and 40-49, which are the economically active population.…”
Section: Discussionsupporting
confidence: 64%